Accuracy of Clinician Predictions of Future Self‐Harm: A Systematic Review and Meta‐Analysis of Predictive Studies. Issue 1 (3rd October 2017) - Woodford, Rachel; Spittal, Matthew J.; Milner, Allison; McGill, Katie; Kapur, Navneet; Pirkis, Jane; Mitchell, Alex; Carter, Gregory
Abstract : Assessment of a patient after hospital‐treated self‐harm or psychiatric hospitalization often includes a risk assessment, resulting in a classification of high risk versus low risk for a future episode of self‐harm. Through systematic review and a series of meta‐analyses looking at unassisted clinician risk classification (eight studies; N  = 22, 499), we found pooled estimates for sensitivity 0.31 (95% CI: 0.18–0.50), specificity 0.85 (0.75–0.92), positive predictive value 0.22 (0.21–0.23), and negative predictive value 0.89 (0.86–0.92). Clinician classification was too inaccurate to be clinically useful. After‐care should therefore be allocated on the basis of a needs rather than risk assessment.